LEGAL IMPLICATIONS ON THE ISSUANCE OF GOVERNMENT REGULATION NO. 36 OF 2021 ON THE WORKER WAGE SYSTEM IN INDONESIA - Bryant Christoper; Kadek Agus Sudiarawan (Transpublika Publisher, 2023)
Wages are something that plays an important role in employment, because wages are a form of appreciation to workers/laborers given by employers for the work that has been done. The purpose of this study is to find out changes in the legal rules regarding the wage system in Indonesia so that workers know how the composition of the calculation used in calculating wages is based on the current legal rules. This research uses normative legal research methods and document study techniques for data collection, as well as legislation and descriptive approaches. The results of this study indicate that this new regulation is aimed at boosting the country's economy and increasing Indonesia's competitiveness in the world by changing the composition of the wage calculation variables and changing the type of wages.